INDIKASI KEPUTUSAN PEMBELIAN KARENA FAKTOR ELECTRONIC WORD OF MOUTH (E-WOM), BRAND IMAGE DAN PRICE DISCOUNT - Dewi, Anita Sumelvia (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH; Vol 1 No 01 (2021): September 2021, 2022)
Electronic Word Of Mouth (e-WOM), Brand Image, and Price Discount are factors that influence the level of purchasing decisions at the Vifa Jaya Bakery bakery business in Banjaranyar Village, Kras District, Kediri Regency. From this, the researchers wanted to prove whether there was an influence of e-WOM, Brand Image, and Price Discount on purchasing decisions. With the results of this research can be used as a reference in policy making and business development in the future. The study sampled 90 respondents. With a population of 900 consumers. Tenik sampling in this study using the technique of Nonprobability sampling (accidental sampling). Data collection techniques use the dissemination of questionnaire questionnaires. The results showed that e-WOM, Brand Image, and Price Discount had a significant effect on purchasing decisions. This can be proven from the correlation result of 0.724, therefore it is said that the relationship between variables is nominated strongly